Phonological Errors In Arabic Pronunciation Among Islamic Speech Contest Participants - Siti Maesaroh; Tatang Tatang; Nalahuddin Saleh (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study explores phonological errors in the pronunciation of Arabic scriptural references by participants in the Islamic Fest 2024 speech contest, analyzing underlying psycholinguistic factors. Employing a descriptive qualitative approach with phonetic and psycholinguistic perspectives, data were collected from two purposively selected participants' speech videos. Analysis involved an observe-and-note technique complemented by Praat software to examine acoustic features. Findings reveal two primary categories of phonological errors: linguistic errors, stemming from inadequate mastery of letter articulation points (makhraj) and vowel length (mad), and performative errors, driven by psychological pressures like nervousness and cognitive load within the competitive context. Both error types influence the conveyed meaning of scriptural references, potentially leading to semantic ambiguity. This study recommends developing da'wah (Islamic preaching) training programs that integrate phonetic, psycholinguistic, and semantic approaches to enhance pronunciation accuracy and semantic clarity in religious communication.